Neat monolayer tiling of molecularly thin two-dimensional materials in 1 min - Matsuba, Kazuaki (Sci Adv, 2017)
Controlled arrangement of molecularly thin two-dimensional (2D) materials on a substrate, particularly into precisely organized mono- and multilayer structures, is a key to design a nanodevice using their unique and enhanced physical properties. Several techniques such as mechanical transfer process and Langmuir-Blodgett deposition have been applied for this purpose, but they have severe restrictions for large-scale practical applications, for example, limited processable area and long fabrication time, requiring skilled multistep operations. We report a facile one-pot spin-coating method to realize dense monolayer tiling of various 2D materials, such as graphene and metal oxide nanosheets, within 1 min over a wide area (for example, a 30-mmφ substrate). Centrifugal force drives the nanosheets in a thin fluid layer to the substrate edge where they are packed edge to edge all the way to the central region, without forming overlaps. We investigated the relationship between precursor concentration, rotation speed, and ultraviolet-visible absorbance and developed an effective method to optimize the parameters for neat monolayer films. The multilayer buildup is feasible by repeating the spin-coating process combined with a heat treatment at moderate temperature. This versatile solution-based technique will provide both fundamental and practical advancements in the rapid large-scale production of artificial lattice-like films and nanodevices based on 2D materials.